Individual Watershed Areas in Sickle Cell Anemia: An Arterial Spin Labeling Study - Stotesbury, Hanne; Hales, Patrick W.; Hood, Anna M.; Koelbel, Melanie; Kawadler, Jamie M.; Saunders, Dawn E.; Sahota, Sati; Rees, David C.; Wilkey, Olu; Layton, Mark; Pelidis, Maria; Inusa, Baba P. D.; et al. (Frontiers in Physiology, 2022)
Previous studies have pointed to a role for regional cerebral hemodynamic stress in neurological complications in patients with sickle cell anemia (SCA), with watershed regions identified as particularly at risk of ischemic tissue injury. Using single- and multi-inflow time (TI) arterial spin labeling sequences (ASL) in 94 patients with SCA and 42 controls, the present study sought to investigate cerebral blood flow (CBF) and bolus arrival times (BAT) across gray matter, white matter with early arrival times, and in individual watershed areas (iWSAs). In iWSAs, associations between hemodynamic parameters, lesion burden, white matter integrity, and general cognitive performance were also explored. In patients, increases in CBF and reductions in BAT were observed in association with reduced arterial oxygen content across gray matter and white matter with early arrival times using both sequences (all p < 0.001, d = −1.55–−2.21). Across iWSAs, there was a discrepancy between sequences, with estimates based on the single-TI sequence indicating higher CBF in association with reduced arterial oxygen content in SCA patients, and estimates based on the multi-TI sequence indicating no significant between-group differences or associations with arterial oxygen content. Lesion burden was similar between white matter with early arrival times and iWSAs in both patients and controls, and using both sequences, only trend-level associations between iWSA CBF and iWSA lesion burden were observed in patients. Further, using the multi-TI sequence in patients, increased iWSA CBF was associated with reduced iWSA microstructural tissue integrity and slower processing speed. Taken together, the results highlight the need for researchers to consider BAT when estimating CBF using single-TI sequences. Moreover, the findings demonstrate the feasibility of multi-TI ASL for objective delineation of iWSAs and for detection of regional hemodynamic stress that is associated with reduced microstructural tissue integrity and slower processing speed. This technique may hold promise for future studies and treatment trials.